Microsoft visual basic design patterns - Stamatkis, Bill.; Stamatakis, William ([S.l.] : Microsoft Press, 2000)
"Microsoft Visual Basic Design Patterns" focuses on how to capitalize on the powerful object-oriented capabilities of Visual Basic. Specifically, the book introduces and explains how to employ a set of reusable software design patterns available within Visual Basic. Design patterns take objects to the next level, encouraging both reuse and more elegant development. While other books have attempted to define a common software development paradigm, their results can be largely categorized as esoteric -- and none have spoken strictly within the context of Visual Basic. The author successfully turns theory into practice, offering 15 fully developed and immediately useful patterns for more productive Visual Basic programming. And because these frameworks are not version-dependent, this book will serve developers working with Visual Basic 5.0, 6.0, and beyond.